(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
English language teaching has undergone tremendous changes over the years, especially the last ten years. Teachers, who practiced Grammar Translation or Classical Method during the previous decades, relied on black board as the apt tool to impart communication skills and the nuances of English language. Later on, the overhead projectors, acted as another medium for the teacher dominated classrooms. Such teachers believed in the dictum of drill and practice. Researchers had given more emphasis on authentic and meaningful contextualized discourse. Then they focused on a successful adult second language acquisition. With the advent of ICT products, it has been made possible for the language teachers to enrich their profession. Basically, the teacher controls the process, the content is delivered to the whole class and the teacher tends to emphasize factual knowledge.